Sistem Pendukung Keputusan untuk Rekomendasi Olahraga Bedasarkan Kondisi KesehatanMenggunakan Metode Analythical Hierarchy Process (AHP) - Kemalasari Siregar, Gunayanti; Pujianto; Ridhawati, Eka (Universitas Muhammadiyah Metro, 2025)
Exercise plays a vital role in maintaining physical health. However, selecting inappropriate types of exercise without considering an individual’s physical condition and medical history may lead to injury or worsen existing health problems. This study aims to develop a decision support system (DSS) that provides exercise recommendations based on the user's health condition. The Analytical Hierarchy Process (AHP) method is applied to weigh criteria according to their relative importance. The criteria considered in this study include age,body mass index (BMI), medical history, and physical fitness level. The exercise alternatives analyzed are running, cycling, swimming, yoga, and brisk walking. The AHP calculation results show that certain health conditions are more suitable for specific types of exercise,each with different priority weights. The proposed DSS can provide personalized and targeted exercise recommendations aligned with the user's condition. This system is expected to assist individuals in making safe and effective exercise decisions